SC24 Improving cardiac arrest response systems in a mental health unit using large-scale in situ simulation. (3rd November 2019) - Creed, Michael; Reid-McDermott, Bronwyn; Costello, Maria; Maher, Senan; O'Grady, Margaret; Byrne, Dara
Abstract : Background: A new Acute Adult Mental Health Unit (AAMHU) recently opened in Galway University Hospital, remote from the main hospital building and replacing the previously co-located unit. Due to infrequency of on-site medical emergencies, and the lack of familiarity of the cardiac arrest team with the location and layout of the AAMHU, concerns were raised with regards response to and management of medical emergencies on-site. In light of this, a large-scale in situ 'mock-code' simulation event was implemented to test the existing cardiac arrest response system, and from that develop recommendations to improve patient safety and quality of care. Summary of project: A multidisciplinary team of physicians, nurses, emergency response staff, a resuscitation officer, security and simulationists collaborated to plan the simulation event. Two mock cardiac arrests were simulated on the top and bottom floor of the unit. The exercise was audio recorded, and observers positioned throughout the AAMHU took field notes on the response of each participating discipline making note of barriers to the delivery of effective care. A multidisciplinary debrief was conducted after each mock code. Data collected were analysed using a thematic content analysis. The findings from the event were compiled as a report for hospital management, with recommendations to improve process and policy regarding emergency response in the AAMHU. The mock cardiac arrests were repeated eight months later to test implementation of recommendations and to assess for improvement in cardiac arrest response. Summary of results: Analysis identified weaknesses in core patient safety themes, namely exchanging information and the need for leadership. Other issues which emerged included challenging building access, outdated equipment, and lack of policy to manage other inpatients during an emergency response. Following implementation of the recommendations, improvement was noted in cardiac arrest response processes during the repeat mock codes. Discussion, conclusions and recommendations: In situ high-fidelity simulation is an acceptable method for evaluating the effectiveness of cardiac arrest response systems. Simulation can have a role in ensuring that facilities are fit for purpose, and in improving emergency responses in new hospital units.